مخطوطة جواب الخروبي للفقيه أحمد بن أبي محلي: التعريف بها وبمضمونها - بن أبي محلي، أحمد بن عبدالله بن محمد، ت. 1022 هـ.; موساوي، مجدوب ولد علي (جامعة معسكر - مخبر البحوث الاجتماعية والتاريخية, 2022)
يتناول مضمون هذا المقال دراسة لمخطوطة (جواب الخروبي) للفقيه أحمد بن أبي محلي السجلماسي المتوفى بمراكش سنة 1021 ه-1612 م؛ وهي مخطوطة متوسطة الحجم تقع في مئة واثنان وستون صفحة موجودة بالمكتبة الوطنية بالرباط –بالمغرب الأقصى– تحت رقم 611 ك، كما توجد نسخة أخرى على شكل ميكروفيلم بنفس الخزانة بدون ترقيم أو رقم تسلسلي. هذه المخطوطة لا زالت غير محققة تضمنت في مجملها العام ردا وإجابة مطولة من صاحبها على رسالة محمد الخروبي الطرابلسي الذي أنكر فيها على شيخه الصوفي أبي عمرو بن أحمد المراكشي. وقد وصفها أحمد بن أبي محلي بالرسالة السفيهة والوقيحة والشنيعة. اجتهد أحمد بن أبي محلي كثيرا في تقديم الدلائل والبراهين وبصفة خاصة من الكتاب والسنة في رده وجوابه على محمد الخروبي وجماعته قصد إقناعهم بأن يعدلوا عما أنكروه في شيخه؛ كما استعمل في جوابه هذا الكثير من الجدل والعنف والسخرية والليونة بحسب الظروف؛ ليظهر بذلك عن جزء مهم من شخصيته ومزاجه. كما ضمت المخطوطة أبوابا وفصولا كثيرة تناولت مسائل عديدة ومتنوعة ومهمة في علم التصوف والحقائق والمعارف وأقاويل أهل العلم والقصص المأثورة من السلف الصالح. سنتطرق في مقالنا هذا إلى عرض هذه الأفكار والمعلومات التي طرحها وعالجها الفقيه أحمد بن أبي محلي السجلماسي؛ من خلال التعريف بهذه المخطوطة وبمضامينها المختلفة وبصاحبها؛ خصوصا وأنها ساهمت في الكشف لنا عن جوانب مختلفة من علاقات العلماء فما بينهم وقصد تعميم الفائدة والاستفادة منها بين الباحثين والمهتمين والدارسين من جهة وإثراء لمكتبتنا الوطنية بالمصادر الأصيلة من جهة ثانية. The content of this article deals with a study of the manuscript of the jawab al-kharoubi manuscript of the jurist Ahmed ibn Abi Mahali Sijjal- al-Massi, who died in Marrakech in 1021 AH-1612 AD. It is a medium-sized manuscript of one hundred and sixty-two pages located in the National Library in Rabat in Morocco under the number 611k. It is still unfulfilled, which included in its general totality a response and a long answer from its owner to the message of Muhammad Al-Kharoubi Al-Tarabulsi, in which he denied his Sufi sheikh Abi Amr bin Ahmed Al-Marakchi. Ahmed bin Abi Mahalli described it as an insignificant, rude, and heinous message. Ahmed bin Abi Mahalli worked hard to provide evidence and proofs, especially from the Quran and the Sunnah in his reponse to Muhammad Al-Kharoubi and his group in order to persuade them to change what they denied in his Sheikh, as he used in his answer a lot of controversy, violence, sarcasm and softness according to the circumstances, to show this for important part Of his personality and temperament. The manuscript also included many chapters that dealt with many, varied and important issues in the science of mysticism, facts and knowledge, the saying of scholars and the stories told from the righteous predecessors. In this article, we will discuss the presentation of these ideas and information presented and processed by the jurist Ahmed bin Abi Mahali Al-Sijilmassi, by introducing this manuscript and its various contents and its owner, especially as it contributed to revealing to us various aspects of the relationships of scientists, what is between them and in order to generalize the benefit from it among researchers And interested and scholars on the one hand and enrich our national library with authentic sources.
Keywords: تحقيق المخطوطات -- علم التصوف -- الفكر الديني -- تراجم الاعلام